PROTECTIVE EFFECT OF BROCCOLI AND FERULIC ACID ON IMIDACLOPRID-INDUCED NEUROTOXICITY IN RAT - Sawsan A. Nasr2Mahgoub M. Ahmed1 (Journal of Biomedical and Pharmaceutical Research, 2017)
Imidacloprid may induce oxidative stress leading to generate free radicals and alternate oxygen free radical scavenging enzyme system. This study aims to investigate the neuroprotective effect of broccoli water extract and ferulic acid on imidacloprid induced oxidative stress and DNA damage in male albino rats. Rats were co-treated with broccoli water extract (200 mg/kg) or ferulic acid (20 mg/kg) with imidacloprid (80 mg/kg) orally for 28 days. The results revealed that imidacloprid induced low serum levels of total antioxidant capacity (TAC), whereas lipid peroxidation (LPO) content was increased. However, administration of broccoli improved these parameters. Broccoli and ferulic acid significantly (P<0.05) attenuated the imidacloprid-induced increases in lipid peroxidation (LPO), tumor necroses factor α (TNF-α) and nitric oxide (NO) contents and myeloperoxidase (MPO), glutathione-S-transferase (GST) and catalase (CAT) activities. Imidacloprid decreased reduced glutathione (GSH) while co-treatment with broccoli and ferulic acid significantly (P<0.05) improved the level of GSH. DNA damage as assessed by 8-hydroxydeoxyguanosine (8-OHdG) level was increased in imidacloprid-treated group. However, DNA damage was decreased in broccoli and ferulic acid treated groups. The possible mechanism of broccoli and ferulic acid extract on imidacloprid might be due to decreasing oxidative stress (LPO, NO and DNA damage) and increasing GSH content. Thus, broccoli and ferulic acid was suggested to protected rat’s liver against imidacloprid-induced oxidative stress and DNA damage in brain. Keywords: broccoli, ferulic acid, imidacloprid, DNA damage, oxidative stress, brain